NURSING CARE FOR ACUTE PAIN RELATED TO GASTRITIS AT ANGGREK ROOM RSI NASHRUL UMMAH LAMONGAN - Al Baihaqi, Rohmat (Universitas Airlangga, 2021)
Introduction: Gastritis is a problem that many people experience and can occur at various ages. The most common symptom for gastritis sufferers is acute pain. However, acute pain nursing care in gastritis patients is different. This study is to explain Acute Pain Nursing Care for Gastritis Clients at Anggrek Room RSI Nashrul Ummah Lamongan. Methods: This study used case study design. Sampling of this study was one child suffering from gastritis with acute pain symptom. Data of this study were collected by interview, observation, physical examination and documentation. The data that obtained were analyzed with descriptive methods, diagnosis and evaluation. Results: The results showed that there were several gaps between case and theories for the assessment stage. A gap occurs in the assessment of the physical examination of the nasal passages which reveals the presence of nasal lobe breathing while holding pain. The priority of nursing diagnosis was acute pain and the focus of interventions was on pain management. Conclusion: Providing implementation of non-pharmacological techniques (distraction and relaxation techniques) and pharmacological (collaboration providing analgesics), environmental management, touch management, providing knowledge of the causes of pain and efforts to reduce pain, and observation of conditions that are effective in reducing pain in patients